Storage evaluation of a functional food with skimmed milk enriched with fatty acids of Sacha Inchi (Plukenetia volubilis L.) - Patrick García; Aníbal Quinteros; Patricia García; Julio Chumacero; Publio Castro (Agroindustrial Science, 2018)
The aim of this study was obtain a semi skim milk enriched with sacha inchi oil (Plukenetia volubilis L.), with sensory acceptability and a suitable storage container. The raw materials used were: fresh semi skim milk of creole cow and virgin sacha inchi oil. The content of polyunsaturated fatty acids raised from 2.8% to 3.0; 3.2% and 3.4% according to the treatment. It was evaluated the sensory microbiological properties of the semi skim milk during its storage period of 30 days. The packaging material used were high density polyethylene container and glass container. The best formulation for semi skim milk was the correspond to 3% of fatty acids stored in glass container which obtained values of: Taste 2.2; Color 2.1; Texture 2.2 and Appearance 2.2 on a maximum of 5.0 units. It is concluded that the production of semi skim milk enriched with fatty acids of sacha inchi is feasible.